Programowanie rozwoju regionalnego w Polsce w dostosowaniu do standardów Unii Europejskiej - Sawicka, Janina (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2003)
Strategic planning and programming process allows the better transfer of information and higher efficiency of decision-making. Poland, like all present European Union Member States is obliged to use multistage development programming. The paper's purpose is to show the system of goals, institutions and instruments within the regional development planning in Poland as well as their progress in adjustment to the European standards. Moreover, the importance of the National Development Plan was shown. This document is of high political weight because after the agreement with European Commission it will constitute the base for preparing the common document known as Community Support Framework which will determine the Community financial contribution to the socio-economic development of Poland in the first years of accession.